Innovative Engineering and Technology III - Lee, Yee Yong (Trans Tech Publications Ltd, Switzerland, 2021)
This journal issue presents materials from the 13th International UNIMAS Engineering Conference 2020 (EnCon 2020), which was held online by University Malaysia Sarawak, Sarawak, Malaysia, with the theme "Empowering industry and transforming society through engineering, technology, and management". The collected papers describe the current research results in the areas of materials engineering and processing technologies with a specific focus on the use of bio- and biodegradable materials in channeling various applications in numerous branches of human activity.